Do Cementless Stems Match Any Hip? A Description of Anthropometric Measurements of the Proximal Femur in Colombia - María Camila Canencio Salgado, MD; Diego Martínez-Villaba, MD; María Bautista, MD MSc; Omar Alejandro Amado Pico, MD (Arthroplasty Today, 2024)
Background: Leg length discrepancy following hip arthroplasty causes dissatisfaction to the patient; thus, preoperative planning and implant selection is critical. The purpose of this study was to measure the articular-trochanteric distance (ATD) and femoral neck length (FNL) in our population and compare them to those of 3 of the most used uncemented stems. Methods: In this cross-sectional study, 401 hip radiographs of healthy adults were collected between January and July 2022. The vertical ATD and FNL were measured. A linear regression model was used to identify the relationship between these measurements and age, sex, and height. A logistic regression model was used to assess the matching of native hips with the neck length of the stem. Results: Mean age was 60 years, and 74.56% were women. In 94.3% of hips, the ATD was negative, 3.73% neutral, and 2% positive. In our population, 0.25% of FNL were shorter than POLARSTEM (Smith & Nephew, UK), 10.72% shorter than MetaFix stem (Corin, UK), and 11.97% shorter than Corail stem (DePuy Synthes, USA). In the logistic regression analysis, matching for the POLARSTEM was associated with age but not with sex or height. Conversely, for MetaFix and Corail, stem matching was associated with sex and height. Conclusions: Anthropometric hip measurements vary among individuals, and variables such as age, sex, and height must be considered during preoperative planning and implant selection to avoid leg length discrepancy. Additional studies, including different implants, are required to guide surgeons in selecting a femoral stem that best matches the patient's native hip.